Effect of the boundary conditions on the Australian uniaxial tension test for softening steel fibre reinforced concrete. (30th September 2018) - Amin, Ali; Markić, Tomislav; Gilbert, R. Ian; Kaufmann, Walter
Highlights: Results are presented on uniaxial tensile tests on twelve identical SFRC "dogbone" specimens tested with end conditions: fixed-fixed (FF); fixed-rotating (FR) & rotating-rotating (RR). The FF condition results in cracking stresses lower than the ones obtained with FR and RR conditions. Specimens with RR end conditions displayed significant out of plane rotation during testing. It is concluded that the FR end conditions serves as a compromise to the issues associated with the other test setups. Abstract: In order to promote the regular use of steel fibre reinforced concrete (SFRC), a rational framework of material models identifying the key material parameters must be established. When considering the design of a structural member manufactured with SFRC, the defining property is its post cracking, or residual, tensile strength. In principle, a direct tension test is the ideal test that should be used in gathering the softening, or residual, parameters of SFRC experimentally. However, there are many parameters which may influence the results of the uniaxial tension test, and the choice of boundary conditions for the test is one of the most relevant ones. Three boundary or end conditions are possible: fixed-fixed, fixed-rotating, and rotating-rotating. In this paper, results of uniaxial tensile tests on twelve identical SFRC "dogbone" specimens tested with the end conditions listed above are presented. Each condition exhibits behaviour not present in the theoretically ideal tensile softening curve. Investigating this is the focus of the present study. It is concluded that the fixed-rotating end conditions serves as a compromise to the issues associated with the other test setups and seems to be more suited for uniaxial tension testing of softening SFRC.